Salt content of instant noodles in Malaysia: a cross-sectional study - Tan, Chun Han; Chow, Zhen Yee; Ching, Siew Mooi; Devaraj, Navin Kumar; He, Feng J.; MacGregor, Graham A.; Chia, Yook Chin (BMJ Publishing Group, 2019)
Objective To determine the salt content in instant noodles sold in Malaysia. Study design A cross-sectional survey was done involving 707 different flavours and packaging of instant noodles sold in six hypermarkets and retailer chains in Malaysia and the corresponding brand's official websites in 2017. Methods The salt content (gram per serving and per 100 g) was collected from the product packaging and corresponding brand's official website. Results Of the 707 different packaging and flavours of instant noodles, only 62.1% (n=439) provided the salt content in their food label. The mean (±SD) salt per 100 g of instant noodles was 4.3±1.5 g and is nearly four times higher than the salt content of food classified in Malaysia as a high salt content (>1.2 g salt per 100 g). The salt content for instant noodle per packaging ranged from 0.7 to 8.5 g. 61.7% of the instant noodles exceeded the Pacific Salt Reduction Target, 11.8% exceeded the WHO recommended daily salt intake of <5.0 per day and 5.50% exceeded Malaysia Salt Action Target. 98% of instant noodles will be considered as high salt food according to the Malaysia Guidelines. The probability of the instant noodles without mixed flavour (n=324) exceeding the Pacific Salt Reduction Target was tested on univariate and multivariate analysis. Instant noodles with soup, Tom Yam flavour, pork flavour and other flavours were found to be predictors of instant noodles with the tendency to exceed Pacific Salt Reduction Target when compared with instant noodles without mixed flavours (p<0.05). Conclusion Only 62% of instant noodles displayed the salt content on their food label. Salt content in instant noodles is very high, with 90% exceeding the daily salt intake recommended by WHO. Prompt action from regulatory and health authorities is needed to reduce the salt content in instant noodles.